FAKTOR-FAKTOR YANG BERKONTRIBUSI TERHADAP TINGGINYA SKOR EPDS PADA IBU NIFAS: A LITERATUR REVIEW - Susanti, Revita; Abriyani, Ni Nyoman Yeyen; Kirana, Desi Nindya (IKES Payung Negeri Pekanbaru, 2025)
Postpartum depression is a common mental health disorder among mothers after childbirth. Early detection using the Edinburgh Postnatal Depression Scale (EPDS) is important, but factors contributing to high EPDS scores vary across populations and cultural contexts. This literature review examines studies from 2020–2025 on determinants of elevated EPDS scores in postpartum women. A review search of PubMed and Elsevier (ScienceDirect) using relevant keywords identified 560 articles, reduced to 448 after removing duplicates. Title and abstract screening produced 80 full-text articles, and 22 met the inclusion criteria: original research, publication in 2020–2025, use of the EPDS, participants ≤12 months postpartum, and English language. Findings show that high EPDS scores are associated with several risk factor groups. Psychological factors include antenatal anxiety or depressive symptoms, emotional stress, and a history of mental illness. Social factors involve limited partner or family support, marital conflict, and domestic violence. Obstetric and neonatal factors include pregnancy complications, cesarean delivery, postoperative pain, infant complications, and NICU admission. Behavioral and demographic factors such as not breastfeeding, formula feeding, low education, extreme maternal age, and low socioeconomic status also contribute. Routine EPDS screening and standardized cut-offs are needed to support early detection and prevention of postpartum depression across diverse cultural settings.